(untitled) (The Conference Hub, 2025)
This research explores the international legal framework governing the extradition of individuals accused or convicted of crimes, emphasizing its significance in strengthening intergovernmental cooperation in criminal justice. The study begins by examining the historical evolution of the extradition institution, from its origins as a politically motivated practice to its current function as a legal mechanism ensuring accountability and justice. Despite growing international collaboration, gaps remain in harmonizing national legislation with international norms—particularly within the legal system of Uzbekistan, where extradition procedures are not yet fully codified or unified under a specific law.